Significant mitigation measures for critical factors of cost overrun in highway projects of Pakistan - Sohu, Samiullah; Abdullah, Abd Halid; Nagapan, Sasitharan; Ahmed Jhatial, Ashfaque; Ullah, Kaleem; Ali Bhatti, Imtiaz (Engineering, Technology and Applied Science Research (ETASR), 2018)
Stakeholders of the construction industry and academia are often facing problems of cost overrun. It has been observed that many constructions of highway projects are not completed at the approved cost due to certain factors. The objective of this research is to identify the cost overrun critical factors involved in highway projects with their significant mitigation measures. In this regard, literature review helped to identify 64 factors of cost overrun. Based on these 64 common factors, a preliminary survey was carried out among 30 selected respondents of highway projects to identify the critical factors of cost overrun and its possible mitigation measures. Results of the preliminary study reported 8 critical factors and 42 possible mitigation measures for the identified factors. Another questionnaire was established on the findings of the preliminary survey and was distributed among 350 stakeholders of highway projects to identify the significant mitigation measures of finding critical factors of cost overrun. In total, 8 significant mitigation measures were identified as causative and critical factors of cost overrun. The findings of this research would be helpful for the construction practitioners who are dealing with cost overrun issues in the highway projects of Pakistan.